Production and validation of recombinant hamster cytokines as tools for immunological studies - Laura de V. Maiocchi; Natasha R. de Oliveira; Mara A. C. Maia; Ana C. K. Pedra; Tiffany T. Bunde; Beatriz C. M. Santos; Izani Bonel Acosta; Antonio Sergio Varela Junior; Odir A. Dellagostin; Thais L. O. Bohn (Molecular Biology Reports, 2026)

A systematic review on the selection of reference genes for gene expression studies in rodents: are the classics the best choice? - Tiffany T. Bunde; Ana C. K. Pedra; Natasha R. de Oliveira; Odir A. Dellagostin; Thaís L. O. Bohn (Molecular Biology Reports, 2024)

Production of recombinant cytokines and polyclonal antibodies for analysis of cellular immune response in golden Syrian hamster - Ana C. K. Pedra; Natasha R. de Oliveira; Mara A. C. Maia; Francisco D. S. Santos; Tiffany T. Bunde; Pedro H. F. C. Souza; Laura de V. Maiocchi; Odir A. Dellagostin; Thaís L. O. Bohn (Molecular Biology Reports, 2024)

Analysis of glucose and xylose metabolism in new indigenous Meyerozyma caribbica strains isolated from corn residues - Viviani Tadioto; Letícia M. Milani; Évelyn T. Barrilli; Cristina W. Baptista; Letícia Bohn; Aline Dresch; Ricardo Harakava; Odinei Fogolari; Guilherme M. Mibielli; João P. Bender; Helen Treichel; Boris U. Stambuk; et al. (World Journal of Microbiology and Biotechnology, 2022)

Correlation between in vitro and in vivo data on food digestion. What can we predict with static in vitro digestion models? - T. Bohn; F. Carriere; L. Day; A. Deglaire; L. Egger; D. Freitas; M. Golding; S. Le Feunteun; A. Macierzanka; O. Menard; B. Miralles; A. Moscovici; et al. (Critical Reviews in Food Science and Nutrition, 2018)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Determination of atrazine and degradation products in Luxembourgish drinking water: origin and fate of potential endocrine-disrupting pesticides - T. Bohn; E. Cocco; L. Gourdol; C. Guignard; L. Hoffmann (Food Additives & Contaminants: Part A, 2011)

Quantitative trait loci analysis of phenotypic traits and principal components of maize tassel inflorescence architecture - N. Upadyayula; J. Wassom; M. O. Bohn; T. R. Rocheford (Theoretical and Applied Genetics, 2006)

Genetic and QTL analysis of maize tassel and ear inflorescence architecture - N. Upadyayula; H. S. da Silva; M. O. Bohn; T. R. Rocheford (Theoretical and Applied Genetics, 2006)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)